Physical Computing Modul for Informatics Learning - Effindi, Muhamad Afif; Handayani, Wuritri (Jurnal Pendidikan Multimedia (Edsence), 2024)
Informatics is a relatively new subject in Elementary and Secondary Education in Indonesia. Referring to the Guidelines for the Implementation of Informatics Content/Subjects of the 2013 Curriculum and related regulations and circulars, the subjects implemented since the 2019-2020 school year must have a School Repository. The Repository contains a collection of Learning Plans, Teaching Materials, and Portfolios that record the implementation of Informatics subjects. The challenge in developing subject material is the need to develop a combination of hardware and software for informatics learning class. This research aims to develop a Physical Computing Teaching Modul in order to answer the challenge. This research method includes a Literature Review, Material Design in the Teaching Module, and the creation of a Teaching Module with attractive packaging suitable for use in class. The research output is a Physical Computing teaching Modul.